Identifying Plant Functional Traits of Weeds in Fields Planted with Glyphosate-Tolerant Maize for Preferable Weed Management Practices - Murendeni Kwinda; Stefan John Siebert; Helga Van Coller; Tlou Samuel Masehela (Agriculture, 2024)
Weed responses in disturbance-prone agroecosystems are linked to specific plant traits that enable their persistence. Understanding how weeds adapt to thrive in these systems in response to herbicide application is important for farmers to improve weed management for enhanced crop productivity. In this study, we investigated the functional traits and types of weed species able to persist within fields of glyphosate-tolerant maize in the Oliver Tambo District of the Eastern Cape Province, South Africa. This was accomplished by exploring the abundance patterns, composition, and richness of specific weed traits and functional types. Frequency measures (%) were used to identify indicator species. A data set comprising 42 indicator weed species and 11 predefined disturbance traits from 28 fields of glyphosate-tolerant maize was considered for functional analysis. Clusters were identified according to the grouping of weed species based on their trait scores, which revealed ten plant functional types (PFTs). Disturbances associated with post-emergence (after ploughing, sowing, and herbicide application) act as filters that select for weed species with traits such as life span, life form, growth form, photosynthetic pathway, carbon storage, and nitrogen-fixing ability to colonise fields. Trait richness did not differ significantly across maize fields. Our results highlighted the functional types and traits that are favourable to weed resistance and survival, and these need to be considered when developing different herbicide application protocols. By understanding which traits are favourable for weed survival post-emergence, farmers can apply targeted weed management to safeguard maize productivity. In addition, successful control of weeds will contribute to landscape-targeted herbicide applications that are less harmful to the environment.